Analisis Personal Branding Pada Kesuksesan Karir Content Creator TikTok - Anisa, Nur; Handayani, Trisni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
In today's era, there are a lot of content creators who are inconsistent in building personal branding, making them not last long in their career development. Content creators who build personal branding must be consistent and have uniqueness in themselves. The purpose of this research is to find out how personal branding satyasalsabila on his TikTok account. The research method used is a qualitative method. The data collection techniques used in this study are interviews, observations, and documentation. Based on the results of data analysis, personal branding satyasalsabila has the competence of singing, cooking, dancing, satyasalsabila's dress style, which is casual and satyasalsabila's standard, namely world life balance. This shows that personal branding is very important in the success of satyasalsabila's career on his TikTok account